2022
DOI: 10.1039/d2qi01796b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cage isomers and magnetic Dy⋯Dy interactions in Dy2O@C88 and Dy2C2@C88 metallofullerenes

Abstract: Three isomers of Dy2O@C88 and two isomers of Dy2C2@C88 were synthesized and structurally characterized by single-crystal X-ray diffraction, vibrational spectroscopy, and DFT calculations. Both types of clusterfullerenes feature 4-fold electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…After inspecting literature, a metal carbide metallofullerene Lu 2 C 2 @ D 2 (35)-C 88 28 and a dimetallofullerene Sm 2 @ D 2 (35)-C 88 , 29 both show almost identical features with Ce 2 O@C 88 . And taking comparison to the recently reported isomers of Dy 2 O@ D 2 (35)-C 88 and Dy 2 C 2 @ D 2 (35)-C 88 , 26 they also show similar absorption features with that of Ce 2 O@C 88 . These results demonstrated that Ce 2 O@C 88 adopts a D 2 (35)-C 88 cage.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…After inspecting literature, a metal carbide metallofullerene Lu 2 C 2 @ D 2 (35)-C 88 28 and a dimetallofullerene Sm 2 @ D 2 (35)-C 88 , 29 both show almost identical features with Ce 2 O@C 88 . And taking comparison to the recently reported isomers of Dy 2 O@ D 2 (35)-C 88 and Dy 2 C 2 @ D 2 (35)-C 88 , 26 they also show similar absorption features with that of Ce 2 O@C 88 . These results demonstrated that Ce 2 O@C 88 adopts a D 2 (35)-C 88 cage.…”
Section: Resultssupporting
confidence: 73%
“…These results indicate the structural similarity between Dy 2 O@C 88 and Ce 2 O@C 88 . 26 Other new types of metal oxide cluster fullerenes have also been reported recently, such as Ho 2 @C 2n (2n = 74, 92, 84), 12,30 Tb 2 O@C 74 , 31 and Lu 2 O@C 80 . 32 Unlike the variable cluster forms observed for Sc, such as Sc 2 O, Sc 2 O 3 , and Sc 4 O 2 , these newly reported molecules adopt an endohedral form identical to that of M 2 O.…”
Section: Synthesis and Characterizationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, various endohedral fullerenes with the general formula of M 2 X@C n have also been prepared to date. [29][30][31][32] Although the large-scale synthesis of the MX@C 70 systems studied here seems to be inaccessible at the moment, molecular surgery methods come across as a step in the right direction. [33][34][35][36] Very recently, Gao et al 37 successfully performed insertion of LiF and [BeF] + into an open-cage C 60 fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various endohedral fullerenes with the general formula of M 2 X@C n have also been prepared to date. 29–32…”
Section: Introductionmentioning
confidence: 99%